International Newborn Screening: Where Are We in Saudi Arabia? - Noara Alhusseini; Yara Almuhanna; Lama Alabduljabbar; Soaad Alamri; Maryam Altayeb; Ghadi Askar; Noor Alsaadoun; Khadijah Ateq; Mariam M. AlEissa (Springer, 2024)
Abstract Newborn screening (NBS) programs are believed to play an important role in the decrease of infant mortality rates in many countries. This is achieved through offering early detection and treatment of many genetic as well as metabolic disorders prior to the onset of symptoms. Our paper examines NBS across seven diverse nations: Saudi Arabia, the United States, Japan, Singapore, Canada, Australia, and the United Kingdom. This paper discusses the diseases screened for by each country, latest additions, as well as future recommendations, when applicable. Employing a comparative approach, we conducted a comprehensive review of the most recent published literature on NBS programs in each country and subsequently examined their latest implemented NBS guidelines as outlined on their respective official government health sector websites. We then reviewed the economic feasibility of each of these programs and factors that affect implementation and overall benefit. While all six countries employ well-developed programs, variations are observed. Those variations are mainly attributed to disparities in access, resource scarcity, financial availability, as well as ethical and cultural considerations. From a local perspective, we recommend conducting further population-based studies to assess the epidemiological data in relation to the disease burden on the country's economy. Moreover, we recommend updating national and international guidelines to contain a more comprehensive approach on policies, operation, and sustainability to deliver a service through the lens of value-based healthcare.